DAMPAK BULLYING TERHADAP KONDISI PSIKOSOSIAL SISWA KELAS II DI SD N SURYODININGRATAN 1 YOGYAKARTA - Ahmad Oktavian Triatmojo; Endang Hangestiningsih (Universitas Sarjanawiyata Tamansiswa, 2019)
This type of research is a type of qualitative research. This research was conducted at SD N Suryodiningrata 1 Yogyakarta. The subjects in this study were to schools, class teachers, and students. Data collection techniques use observation, interview, and observation techniques. Based on the results of the study show that the forms of student bullying behavior that occur are that students make fun of and mock friends, find out friends and ask for pocket money to their friends. The way the class teacher handles student bullying behavior is by conducting classical and individual guidance. The role of the class in addressing the behavior of bullying students, be a mediator when the bullying occurred in class, and give advice as well as motivations to students.